Pathology of Persian Translations of Texts and Research on Iran-China Relations: With Emphasis on the Critique on the Book Ancient Texts on China-Iran Relations - Hamidreza Pashazanous (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
A considerable part of our knowledge about Iran and its relations with other neighboring civilizations has been based on Greek and Roman texts and sources, some of which have been translated into Persian with acceptable quality. However, there is important information about ancient Iran in the historical texts and archaeological findings discovered in the Far East, especially China. A small number of them have been translated into Persian, which contains errors. Therefore, considering the importance of historical texts and archeological data related to Iran in China, the present article intends to first examine the works related to ‘Iranian-Chinese Relations’, in order to pathologize the Persian translations of these texts and research on Iran-China relations. Then, it seeks to criticize the part related to ancient Iran in the book Ancient Texts on China-Iran Relations. The most important outcome of this study is the weakness of translators and editors in translating Chinese texts and research into Persian, which in some cases, these weaknesses are the result of important mistakes of the authors of the research in the West.